G362(P) Child nutrition: a "need to feed" future doctors. (27th April 2015) - Bali, S; Jacob, H; Fertleman, C
Abstract : Aims: Parents may ask doctors working in a range of specialties for advice on childhood nutrition. The Department of Health states that all doctors working with children should engage in health promotion. Ensuring the provision of high quality information may help prevent obesity and optimise the health of children and young people. As many doctors may have limited postgraduate exposure to paediatrics, medical school is an ideal time to learn about the importance of childhood nutrition. We decided to explore the knowledge, skills and attitudes of medical students about providing guidance on childhood nutrition. Methods: We sent a survey to all medical students undertaking their paediatric placement at one teaching hospital between 2012–13. We asked the students whether they felt comfortable advising about breastfeeding, infant and toddler nutrition, obesity, food allergies and infant weighing schedules. We also enquired from them about maternal alcohol consumption during breastfeeding and about a crying baby whose mother was struggling to breastfeed. We collected data using software from SurveyMonkey™ and analysed it using Microsoft Excel™. Results: 82 students were asked to fill in the survey. 47(57%) responded. 32(68%) felt uncomfortable advising about breastfeeding and toddler nutrition. Despite this, 33(70%) felt they would advise a mother struggling with breastfeeding rather than referring her to the health visitor. 32(68%) and 26(55%) thought that with help they could provide information about obesity and food allergies respectively. Regarding maternal alcohol consumption whilst breastfeeding 27(57%) knew the appropriate advice about drinking minimally or in moderation. 43(88%) of the students wanted these topics covered during medical school. A recent survey of 56 UK paediatricians and general practitioners rated the importance of undergraduate knowledge of normal feeding 3.9/5 and ability to engage in health promotion 3.8/5. Conclusions: This study demonstrates a lack of confidence and competence among medical students to provide advice about childhood nutrition, despite clinicians considering the topic essential undergraduate knowledge. Concerted efforts must be made to improve the quality of nutrition and health promotion advice to parents and undergraduate training provides an ideal opportunity to develop these skills.